HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN TINDAKAN PERSONAL HYGIENE SAATMENSTRUASI PADA REMAJA PUTRI - Husni, Husni (JURNAL MEDIA KESEHATAN, 2018)
One of the effects is not maintaining hygiene during menstruation is able to hit kankes Rahim neck (cervical). Based on data from the World Health Organization (WHO), cervical cancer is the second most cancer in women aged 15-45 years after breast cancer. No less than 500,000 new cases with 280,000 patient deaths occur each year worldwide. Indonesia was ranked first by the victims died at least 555 women per day and 200,000 women annually. This study aims to determine the correlation between knowledge and attitude towards personal hygiene during menstruation action at SMAN 2 Bengkulu City. This research is descriptive analytic. The number of respondents 84 people with a sampling technique that stratified random sampling. Presentation of data is done by using a frequency distribution table. The collection of data taken using a questionnaire. The data were analyzed using univariate and bivariate analysis with Chi-Square.The results showed that the respondents are classified as good knowledge of (54.8%), attitude unfavorabel or does not support (53.6%), and the biggest acts (52.4%) is good. From the bivariate analysis were found no correlation between knowledge against acts of personal hygiene during menstruation (p = 0.794), and no relation attitude towards personal hygiene actions during menstruation (p = 0.975).Required role of schools, educators, parents to be more proactive in enhancing knowledge and useful information about the process of menstruation and how to maintain hygiene during menstruation.